Analysis Of Sharia Based Micro Funding Enterprises To Increase Income Of Bmt Al Rifa'ie Customers - Isa Kholili; M. Rihal Irsyada (International Journal of Economic Research and Financial Accounting, 2024)
The aim of this research is to find out the extent of BMT Al Rifa'ie's active role in managing funds through the funding sector and its impact on microeconomic activities for BMT Al Rifa'ie customers.The research method used in this case is descriptive analysis of case studies at BMT Al Rifa'ie. From the results of distributing questionnaires that were carried out to determine the characteristics of respondents in terms of gender, 74% were women and 26% were men, 13% aged 17-29 and 51% aged 30-40, 76% high school education level and 76% bachelor's degree. as much as 21%, and the professional level, namely private employees 43%, self-employed 22%, farmers 32% and civil servants 3%.The results obtained from the analysis above show that the highest financing was in Mudharabah Hijrah 1,915, Mudharabah Fitrah 112, Mudharabah Qurban 8, Mudharabah Hajj & Umrah 13, Mudharabah Terjangka 5, Mudharabah Financing 19